Comparative study of endoscopic tympanoplasty and conventional tympanoplasty - Aggarwal, Priyanka; Sohal, Barjinder Singh; Goyal, J. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: To compare the results of endoscopic tympanoplasty with that of conventional tympanoplasty and to evaluate and compare the graft uptake in both of these methods. The study was done to evaluate the improvement in hearing after tympanoplasty and the problems faced while doing the endoscope assisted tympanoplasty. Methods: Between July 2010 to June 2013, 50 patients underwent tympanoplasty, 25 were endoscope assisted (group A) and 25 were microscope assisted (group B). Results of surgery were compared at the end of three and six months post operation. Results: The success rate in terms of graft uptake rate was 88% with endoscope assisted tympanoplasty and 84% with other microscope assisted tympanoplasty. Overall success rate was 86.0%. Mean hearing improvement was (16.24±10.21 dB) and (14.28±7.10 dB) in group A and group B respectively. Conclusions: Tympanoplasty with its visualization of hidden corners, justifies tympanoplasty by using endoscope in selected cases with comparable improved results in the literature. Furthermore, the cost of the endoscope is much less (about 10%) in comparision to operating microscope, making it more cost effective in developing countries. However, the endoscope cannot be employed in every case as one hand is blocked. In terms of Patient comfort, the endoscope assisted outnumbers the benefits of other conventional methods.